2009
DOI: 10.1016/j.neubiorev.2009.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Basal ganglia mechanisms underlying precision grip force control

Abstract: The classic grasping network has been well studied but thus far the focus has been on cortical regions in the control of grasping. Sub-cortically, specific nuclei of the basal ganglia have been shown to be important in different aspects of precision grip force control but these findings have not been well integrated. In this review we outline the evidence to support the hypothesis that key basal ganglia nuclei are involved in parameterizing specific properties of precision grip force. We review literature from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
81
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(90 citation statements)
references
References 108 publications
(121 reference statements)
8
81
1
Order By: Relevance
“…Moreover, a correlation between BG activity and the velocity or amplitude of the movement was shown in normal subjects using PET (Thobois et al, 2007;Turner et al, 2003) or fMR imaging (Grafton and Tunik, 2011). Prodoehl et al (2009) proposed that dorsal BG (including the internal pallidum) also regulate the parametrization of grip force, whereas changes in fMRI BOLD signal in the ventral BG scale with the prediction of force amplitude (Vaillancourt et al, 2004(Vaillancourt et al, , 2007. Based on these observations it has been suggested that basal ganglia output regulates (among other behavioral and sensory dimensions) movement gain (Turner and Desmurget, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a correlation between BG activity and the velocity or amplitude of the movement was shown in normal subjects using PET (Thobois et al, 2007;Turner et al, 2003) or fMR imaging (Grafton and Tunik, 2011). Prodoehl et al (2009) proposed that dorsal BG (including the internal pallidum) also regulate the parametrization of grip force, whereas changes in fMRI BOLD signal in the ventral BG scale with the prediction of force amplitude (Vaillancourt et al, 2004(Vaillancourt et al, , 2007. Based on these observations it has been suggested that basal ganglia output regulates (among other behavioral and sensory dimensions) movement gain (Turner and Desmurget, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The basal ganglia have long been associated with the scaling of effort or force. Imaging studies in healthy humans have suggested that basal ganglia nuclei, in particular the internal portion of the globus pallidus and the subthalamic nucleus (STN), are involved in encoding gripping force amplitude and rate (Spraker et al, 2007;Prodoehl et al, 2009). Neuronal recordings in monkeys have also suggested that the basal ganglia play an important role in the control of the scaling of motor responses measured in terms of their amplitude or velocity (DeLong et al, 1984;Turner and Anderson, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The basal ganglia are involved in the control of precision grip force, and both are disturbed in HD patients (Prodoehl et al 2009). We found a significant improved performance on the grid force of R6/2 treated with AdB which could be explained by a recovery of striatal functioning compared with AdZ control mice.…”
Section: Discussionmentioning
confidence: 99%